The potential of Ecotourism in Brazil: Chapada dos Veadeiros (GO), Pantanal Mato-Grossense (MT), e Vale do Ribeira (SP) - Simas de Andrade, Paula (Sustainability in Debate, 2013)
Brazil has a variety of biomes with great potential for ecotourism. They include plateaus, waterfalls, beaches, sand dunes, native forests, mountains and other attractions in regions that are home to poor populations struggling to make their living on smallholder agriculture and that frequently do not have their land rights guaranteed. Implementing ecotourism in these regions can mean environmental preservation and a more sustainable livelihood for the local population. The government has a fundamental role to leverage this activity, providing the means to stimulate sustainable forms of agriculture and infrastructure construction parallel to ecotourism. It is also important to train community members to ensure environmental preservation and well serve the visitors, in addition to implementing measures such as waste recycling and efficient water use.